Legislative administration of public affairs aid in the field of human consumption as the instrument of the state policy - Demydenko, L. (Land Management, Cadastre and Land Monitoring, 2018)
The article analyzes normative documents according to which economic incentives can become state aid, ways of developing European and national policies that allow the allocation of state aid for environmental protection and protected areas, and the promotion of biodiversity conservation on legal grounds.    Keywords: state aid, environmental land use, ecological tax, biodiversity conservation, protected areas.